GINGER IN PREGNANT WOMEN WITH EMESIS - Ariani Fatmawati; Rani Sopiah Septianilova; Bhekti Imansari (Journal of Maternity Care and Reproductive Health, 2022)
One of the complaints in pregnancy is nausea and vomiting or emesis of gravidarum that occurs in the first trimester of pregnancy. Ginger is one of the herbal plants that are often used to treat nausea and vomiting. This study aims to identify the effect of giving ginger on the reduction of emesis of gravidarum in first trimester pregnant women. The research design used the evidence -based nursing method using Google Scholar, PubMed, and ProQuest databases. The search was conducted in March and found 10 relevant articles. The inclusion criteria were that the population was pregnant women in the first trimester, using ginger intervention, with a quasi-experimental research design, and randomized control and trial, published in 2016-2021, using Indonesian or English. The results of the literature study showed that giving ginger affects decreasing the frequency of emesis of gravidarum in first trimester pregnant women. Ginger can be given in the form of drinks, aromatherapy, and ginger biscuits. The results showed that ginger can be given twice a day for 4-15 days. Suggestions that the administration of ginger can be done by pregnant women independently at home, by paying attention to the dose, processing method, frequency, and duration of ginger.